The Contingency of the Lifeworld in a World of Standards. Repertoires of Resignification in (Evidence-Based) Healthcare Organization - Lusardi, Roberto (Frontiers in Communication, 2020)
In this article I discuss the irremediable tension between the universalistic dimension of contemporary medicine, represented by the paradigm of evidence-based medicine (EBM), and local daily practices in specific healthcare organizations. This tension constantly challenges the unitary, universalistic vision to which modern medicine and science aspire. The EBM paradigm, which is currently the most prevalent in every medical-nursing discipline, aims to standardize care procedures through the process of constant scientific literature review and the production of operational guidelines based on what epistemic communities define as the most reliable and effective results: the so-called gold standards. In everyday clinical, therapeutic, and care activities, these procedures are intertwined with the multiplicity of elements that make up the lifeworld. “Universalistic” premises are never merely “applied” to “local” interactive contexts but are always creatively “implicated” in them. Using data collected during a year of ethnographic research in an intensive care unit in Northern Italy, I discuss how the abstract indications of EBM and the formal dimension of health organizations are incorporated, through socially located interactive repertoires, in actual care trajectories. Following the Science and Technology Study perspective in a practice-based analysis of daily work, I show how interactions between human actors, technological artifacts and organizational apparatus in daily practices constitute repertoires of resignification through which local universality emerges, resolving the tension between medicine’s universalistic aspirations and the unpredictable, situated nature of the lifeworld. I consider two repertoires: the interpretative (examining the production and dissemination of knowledge) and the relational (focusing on informal interactions between different professional groups and communities of practice). The article shows how care practices cannot disregard the specific organizational conditions in which they unfold and suggests that research should develop reflective analysis skills on what Annemarie Mol calls the logic of care, thus ceasing to treat the local dimension as a disturbing element in formal systems but, on the contrary, taking note of its impact and unavoidability in actual practice.